Determination of quality parameters of gilthead sea bream (Sparus aurata) fillets coated with electrospun nanofibers - Ceylan, Zafer; Sengor, Gulgun F. Unal; Basahel, Abdulrahman; Yilmaz, Mustafa Tahsin (WILEY, 2018)
Practical applications The changes in texture, color, and odor parameters of the samples (C: uncoated samples, CN: the group coated with chitosan-based nanofibers, TLCN: the samples coated with thymol-loaded chitosan-based electrospun nanofibers) were tested. The changes in color of the groups were defined by using L* (lightness), a* (red/green), and b* (blue/yellow) parameters for pH values of C, CN, and TLCN. In terms of microbial spoilage, psychrophilic bacteria counts (TPBc) of the samples were revealed during storage period. The results of microbiological, sensory, and psychochemical analysis demonstrated that CN and TLCN were both effective against rapid deterioration, exhibiting up to 100% limitation of deterioration; furthermore, TLCN was more effective than that of CN samples. The study results suggested that coating of gilthead sea bream fillets with CN and TLCN would be a promising approach to delay the rapid deterioration in sensory properties (odor, texture, and color) and the delay bacteria growth. Also, the rapid changes in the physicochemical quality parameters (pH, L*, a*, and b*) of fish fillets were controlled by using electrospun nanofiber coating technique. Coating of the fish fillets with chitosan-based nanofibers delayed the deterioration. Thymol-loaded chitosan-based nanofibers were more effective to delay the deterioration. Applied tests revealed almost 100% difference between groups.
Keywords: SILVER CARP; SHELF-LIFE; CHITOSAN; FISH; ENCAPSULATION; Biotechnology & Applied Microbiology; Food Science & Technology